Horticulture Revolution for the Poor : Nature, Challenges and Opportunities - Ali, Mubarik (Washington, DC: World Bank, 2012)
Growth in the horticulture sector, after taking off in the mid-1990s, has encouraged growth in horticultural trade, per capita availability and share in farming systems. Developing countries, especially China, have benefited from the horticulture sector expansion. The Horticultural Revolution (HR) benefited the poor by generating employment and income opportunities; improving resource use efficiency; encouraging commercialization in agriculture; and enhancing the availability of health-promoting micronutrients. This study describes the differential scenarios that instigated HR in the 1990s and the Green Revolution (GR) of the 1960s and 1970s. Learning from the lessons of the GR, this paper highlights the challenge of making the HR available to the poor and suggests policies that will provide support through research and public-private partnerships. It concludes that, to expand and deepen the participation of the poor in HR, research should identify niche horticulture markets; find appropriate technological solutions; innovate market arrangements to ensure input supplies and efficient output delivery systems; and link small farmers with the market.